EFFECT OF HYALURONIC ACID ON THE HEALING OF COLONIC ANASTOMOSIS IN RATS TREATED WITH CORTICOID - Campinho Braga de Araújo Lima, Iana; Medeiros Azevedo, ´´Italo; Borges Ferreira Rocha , Keyla; Cunha Medeiros, Aldo (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
Objective: This study aimed at examining whether topical treatment of colon anastomosis with hyaluronic acid can influence the healing of colonic anastomosis in rats treated with systemic corticosteroid. Methods: Three groups of Wistar rats weighing 252 ± 7g were used, with six rats each, all submitted to anastomosis of the proximal colon: Group 1 - control rats, without treatment. Group 2 - rats treated with subcutaneous (s.c) corticosteroid, and topical application of 0.9% saline solution over the anastomosis. Group 3 - rats treated with corticosteroid s.c. and topical application of 0.4% hyaluronic acid (10 mg/ml) on colonic anastomosis. On the 7th postoperative day, under anesthesia and laparotomy, the anastomosis site was subjected to the determination of rupture pressure. Then, samples containing the anastomosis site were resected and fixed in 10% buffered formaldehyde and embedded in paraffin. Masson H-E and trichrome staining. Histometry evaluated the infiltration of inflammatory cells at the anastomosis site, using a numerical scale from 0 to 4. Continuous variables were assessed using the Tukey test. Differences considered significant with p<0.05. Results: All animals survived the experiments. There were no abscesses, fistulas and macroscopically detectable dehiscences in the anastomosis site. The weight of the animals on the 7th postoperative day showed a statistically significant difference (p<0.001) between the control (253.6±6.3g) and corticoid (221.6±15.4g) groups, as well as between the corticoid +. hyaluronic acid group (257.8±9.7g) and corticosteroids (221.6±15.4). There was no significant difference in the comparison between the control and corticoid + hyaluronic acid groups (p>0.05). In the analysis of intraluminal pressure of colonic anastomosis, there was a statistically significant difference when comparing groups 1 (286.8±9.9 mmHg) and 2 (155±6.0 mmHg), 1 (286.8±9,9 mmHg) and 3 (199.1±7.7) and 2 (155±6.0 mmHg) and 3 (199.1±7.7), with p<0.001 for all comparisons. Histopathological classification by the numerical scale: Group 1 - inflammatory response (H-E) grade 3 and collagen deposition by Masson Trichomic grade 1; Group 2 - inflammatory response (H-E) grade 4 and deposition of collagen and fibroblasts by Masson's Trichrome grade1\2; Group 3 - inflammatory response (H-E) grade 3 and deposition of collagen and fibroblasts by Masson's Trichrome grade 1\2. There was no significant difference between groups. Conclusion: The topical use of hyaluronic acid has a positive influence on the initial healing phase of colonic anastomosis in rats treated with systemic corticosteroid.